Consistency of dark skeletal muscles in Thai native black-bone chickens ( Gallus gallus domesticus ) - Kriangwanich, Wannapimol; Piboon, Promporn; Sakorn, Wirakorn; Buddhachat, Kittisak; Kochagul, Varankpicha; Pringproa, Kidsadagon; Mekchay, Supamit; Nganvongpanit, Korakot (PeerJ (San Francisco, CA), 2021)
Black-bone chickens ( Gallus gallus domesticus ) have become economically valuable, particularly in Southeast Asia as a consequence of popular traditional Chinese medical practices. Chickens with whole body organ darkness are considered to have higher value and are, therefore, more often requested. This research study aimed to investigate the darkness in 34 skeletal muscles of 10 Thai black-bone chickens (five males and five females). The evaluation of muscle darkness was done on two levels: (i) a color chart was employed at the macroanatomical level and (ii) by using melanin pigment to evaluate the structure at the microanatomy level. The results revealed that the accumulation of melanin pigment in the muscle tissue was observed in the endomysium, perimysium and epimysium. With respect to the results of the color chart test, iliotibialis lateralis pars preacetabularis, gastrocnemius, fibularis longus and puboischiofemoralis pars medialis showed the highest degree of darkness, while serratus profundus, pectoralis, iliotibialis cranialis, flexor cruris lateralis, and flexor cruris medialis appeared to be the least dark. In addition, we found that the highest and lowest amounts of melanin pigment was noted in the flexor carpi ulnaris and pectoralis ( p < 0.05), respectively; however, there was no significant difference ( p > 0.05) observed between the sexes. These results reveal that the 34 specified muscles of black-bone chickens showed uneven distribution of darkness due to the differing accumulations of melanin pigments of each muscle.This information may provide background knowledge for a better understanding of melanin accumulation and lead to breeding improvements in Thai black-bone chickens.